Trade liberalization and optimal taxation with pollution and heterogeneous workers - Bontems, Philippe; Gozlan, Estelle (Toulouse, 2014)
"In this paper, we address two questions: (i) how should a government pursuing both environmental and redistributive objectives design domestic taxes when redistribution is costly, and (ii) how does trade liberalization affect this optimal tax system, and modify the economy's levels of pollution and inequalities ? Using a general equilibrium model under asymmetric information with two goods, two factors (skilled and unskilled labor) and pollution, we fully characterize the optimal mixed tax system (nonlinear income tax and linear commodity and production taxes/subsidies). We provide simulations highlighting the linkages between pollution, labor income redistribution and increasing globalization with our endogenous fiscal system. In the redistributive case (i.e. in favor of the unskilled workers) and when the dirty sector is intensive in unskilled labor, we show that (i) trade liberalization involves a clear trade-off between the reduction of inequalities and the control of pollution when the source of externality is mainly production ; this is not necessarily true with a consumption externality; (ii) under openness to trade, the source of the externality matters for redistribution, while it is not the case in autarky. Finally we discuss the impact of an increasing willingness to redistribute income and of a technological shock affecting emissions intensity."